EFFICACY OF FOGGING ON CORN KERNELS TO BIOLOGICAL PERFORMANCE OF MAIZE WEEVIL, SITOPHILUS MAIZE L - Setyaningrum, Haris (Science Education, Institut Agama Islam Negeri Ponorogo, 2023)
Natural grain's fogging is a Indonesian traditional method which applied since many years ago. Recently, no specific research was approving this method, especially for maize. Maize weevil, Sitophilus maize L is a common destructive insect pest considered many losses on stored grains. The aim of this research is to determined fogging effect on grains to biological effect of S.maize L. This research conducted using a complete randomized design with three levels of fogging durations 0, 15, 30, 45 minutes with three replications. Observation factors were weevil behavior (S.maize L), frasses, and grain level infestation. The results showed that the level of infestation decreased as well as the increasing of fogging duration. Fogging is a good method for safeness of weevil control on stored grain. Formaldehyde in fog affected prevents grains from attacking weevil. Fogging is a cheap and safe control method regarding the environmental issues